PENINGKATAN KETERAMPILAN MENCERITAKAN PENGALAMAN MELALUI METODE PEMBELAJARAN BERMAIN PERAN SISWA KELAS III SD TIRTOMULYO BANTUL TAHUN AJARAN 2014/2015 - Nur Samsiyati; C. Indah Nartani (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Abstract: The purpose of this research was to describe the increase of telling experience skills through role play methods in III grade students of SD Tirtomulyo Bantul academic year 2014/2015. This methods of this research was Classroom Action Research. The quantitative data analysis was used to analyze the test results and qualitative was used to analyze the result of observation. Based on observation of the learning process, the students ability to tell the esxperience increased after using role play methods. The success or increasing the quality of learning seen from the learning process and increasing students learning behaviors of each cycle. The average score of the test telling experience skillswas increased after actioning in cycle I and cycle II. The average value in pra-action which was 65,29 increased to 67,65 in cycle I. In cycle II increased to 72,69. Percentage of students obtained KKM also increased. In pra-action percentage reached 41.18%, in the cycle I increased to 47.06% and the cycle II becomes 76.47%. It shows that the method of learning role play has a positive effect that is the result of an increase in the test telling experience skills of III grade students of SD Tirtomulyo Bantul academic year 2014/2015.Â